Prevalence of musculoskeletal disorders (MSDS) among primary school female teachers in Terengganu, Malaysia - Alias, Ayuni Nabilah; Karuppiah, Karmegam; How, Vivien; Perumal, Velu (Elsevier, 2020)
Musculoskeletal disorders (MSDs) has been a well-known occupational health issue for workers over recent years, and the prevalence among school teachers is particularly high. In Malaysia, few studies are focusing on MSDs and associated factors among school teachers, but in Terengganu, there is no data available for MSDs among school teachers. Objectives: To identify the prevalence of MSDs and associated risk factors among female teachers in Terengganu primary school. Methods: Data collection was carried out with a self-administered questionnaire. A total of 212 female school teachers participated in this study. Results: The findings show that the prevalence for any parts of the body was 40.1%. The most affected part of the body was feet, with 32.5% for the past 12-months and 36.8% for the past 7 days. The most significant risk factors that associated with body parts (lower back, thigh, calf, knee, and feet) were age, BMI, sports activity, shoe type, teaching hours, and standing hours during school. Conclusion: Female teachers in Terengganu's primary school had shown a significant prevalence of musculoskeletal disorders. The most affected body parts were feet, followed by knee, upper back, and lower back. Related risk factors such as age, BMI, sports activity, type of shoe, teaching hours and standing hours were analysed. Hence, they are prone to have higher MSDs prevalence than current results due to significant risk factors if there is no measure taken to reduce MSDs prevalence among teachers.